Question
upstudy study bank question image url

Determine the general solution of \( \cos x-\sin x=\sqrt{2} \)

Ask by Goodwin Hamilton. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The general solution is \( x = \frac{7\pi}{4} + 2k\pi \), where \( k \) is any integer.

Solution

Solve the equation \( \cos(x)-\sin(x)=\sqrt{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\cos\left(x\right)-\sin\left(x\right)=\sqrt{2}\) - step1: Move the expression to the right side: \(-\sin\left(x\right)=\sqrt{2}-\cos\left(x\right)\) - step2: Move the expression to the left side: \(-\sin\left(x\right)-\sqrt{2}=-\cos\left(x\right)\) - step3: Raise both sides to the \(2\)-th power\(:\) \(\left(-\sin\left(x\right)-\sqrt{2}\right)^{2}=\left(-\cos\left(x\right)\right)^{2}\) - step4: Calculate: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2=\cos^{2}\left(x\right)\) - step5: Rewrite the expression: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2=1-\sin^{2}\left(x\right)\) - step6: Move the expression to the left side: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2-\left(1-\sin^{2}\left(x\right)\right)=0\) - step7: Calculate: \(2\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+1=0\) - step8: Solve using the quadratic formula: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{\left(2\sqrt{2}\right)^{2}-4\times 2}}{2\times 2}\) - step9: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{\left(2\sqrt{2}\right)^{2}-4\times 2}}{4}\) - step10: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{0}}{4}\) - step11: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm 0}{4}\) - step12: Separate into possible cases: \(\begin{align}&\sin\left(x\right)=\frac{-2\sqrt{2}+0}{4}\\&\sin\left(x\right)=\frac{-2\sqrt{2}-0}{4}\end{align}\) - step13: Simplify the expression: \(\begin{align}&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\\&\sin\left(x\right)=\frac{-2\sqrt{2}-0}{4}\end{align}\) - step14: Simplify the expression: \(\begin{align}&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\\&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\end{align}\) - step15: Evaluate the logic: \(\sin\left(x\right)=-\frac{\sqrt{2}}{2}\) - step16: Use the inverse trigonometric function: \(x=\arcsin\left(-\frac{\sqrt{2}}{2}\right)\) - step17: Calculate: \(\begin{align}&x=\frac{7\pi }{4}\\&x=\frac{5\pi }{4}\end{align}\) - step18: Add the period: \(\begin{align}&x=\frac{7\pi }{4}+2k\pi ,k \in \mathbb{Z}\\&x=\frac{5\pi }{4}+2k\pi ,k \in \mathbb{Z}\end{align}\) - step19: Rewrite the expression: \(x=\left\{ \begin{array}{l}\frac{5\pi }{4}+2k\pi \\\frac{7\pi }{4}+2k\pi \end{array}\right.,k \in \mathbb{Z}\) - step20: Check the solution: \(x=\frac{7\pi }{4}+2k\pi ,k \in \mathbb{Z}\) The general solution of the equation \( \cos x - \sin x = \sqrt{2} \) is \( x = \frac{7\pi}{4} + 2k\pi \), where \( k \) is an integer.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( \cos x - \sin x = \sqrt{2} \), we can first rearrange it as: \[ \cos x = \sin x + \sqrt{2} \] Next, we can utilize the identity for the sine and cosine function to write: \[ \cos x - \sin x = \sqrt{2} \implies \frac{\sqrt{2}}{2} \cos x - \frac{\sqrt{2}}{2} \sin x = 1 \] This can be rewritten as: \[ \sqrt{2} \left( \frac{1}{\sqrt{2}} \cos x - \frac{1}{\sqrt{2}} \sin x \right) = 1 \] Recognizing \( \frac{1}{\sqrt{2}} \) as \( \cos\left(\frac{\pi}{4}\right) \) and \( \sin\left(\frac{\pi}{4}\right) \), we can express this in a unified way: \[ \sqrt{2} \left( \cos\left(x + \frac{\pi}{4}\right) \right) = 1 \] Dividing both sides by \( \sqrt{2} \), we get: \[ \cos\left(x + \frac{\pi}{4}\right) = \frac{1}{\sqrt{2}} = \cos\left(\frac{\pi}{4}\right) \] This leads us to the general solutions: \[ x + \frac{\pi}{4} = 2n\pi \pm \frac{\pi}{4} \quad (n \in \mathbb{Z}) \] This simplifies to: 1. \( x = 2n\pi \) (for the plus sign) \( - \frac{\pi}{2} \) 2. \( x = 2n\pi - \frac{\pi}{2} - \frac{\pi}{4} \) \( = 2n\pi - \frac{3\pi}{4} \) So the general solutions are: \[ x = 2n\pi - \frac{\pi}{2} \quad \text{and} \quad x = 2n\pi - \frac{3\pi}{4}, \, n \in \mathbb{Z} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy